Evaluation of the Gang Resistance Education and Training (GREAT) Program in the United States, 1995-1999 - Esbensen, Finn-Aage ([Verlag nicht ermittelbar], 2002)
This study sought to evaluate the effectiveness of the Gang Resistance Education And Training (GREAT) program by surveying five different groups: students in a cross-sectional design (Part 1), law enforcement officers (Part 2), educators (Part 3), parents (Part 4), and students in a longitudinal design (Part 5). Middle school students in the cross-sectional design were surveyed to examine GREAT's short- and long-term effects, and to assess the quality and effectiveness of officer training. Law enforcement officers were surveyed to determine whether their perceptions and expectations of the GREAT program varied depending on sex, race, rank, age, level of education, and length of time working in policing. Data were collected from middle school personnel (administrators, counselors, and teachers) in order to assess educators' attitudes toward and perceptions of the effectiveness of the GREAT program, including the curriculum's appropriateness for middle school students and its effectiveness in delinquency and gang prevention both in the school and in the community. Parents were surveyed to assess their attitudes toward crime and gangs in their community, school prevention programs, the role of police in the school, and their satisfaction with and perceptions of the effectiveness of the GREAT program. The middle school students participating in the longitudinal aspect of this study were surveyed to examine the change in attitudes and behavior, germane to gang activity, over time. Variables for all parts were geared toward assessing perception and attitudes about the police and the GREAT program and their overall effectiveness, community involvement, neighborhood crime, and gang-related activities.